Computer Aided Modeling of Human Mastoid Cavity Biomechanics Using Finite Element Analysis. (4th August 2009) - Lee Lee, Chia-Fone Chia-Fone; Chen Chen, Peir-Rong Peir-Rong; Lee Lee, Wen-Jeng Wen-Jeng; Chou Chou, Yuan-Fang Yuan-Fang; Chen Chen, Jyh-Horng Jyh-Horng; Liu Liu, Tien-Chen Tien-Chen
Abstract : The aim of the present study was to analyze the human mastoid cavity on sound transmission using finite element method. Pressure distributions in the external ear canal and middle ear cavity at different frequencies were demonstrated. Our results showed that, first, blocking the aditus improves middle ear sound transmission in the 1500- to 2500-Hz range and decreases displacement in frequencies below 1000 Hz when compared with the normal ear. Second, at frequencies lower than 1000 Hz, the acoustic pressures were almost uniformly distributed in the external ear canal and middle ear cavity. At high frequencies, higher than 1000 Hz, the pressure distribution varied along the external ear canal and middle ear cavity. Third, opening the aditus, the pressures difference in dB between the middle ear cavity and external ear canal were larger than those of the closed mastoid cavity in low frequency (<1000 Hz). Finally, there was no significant difference in the acoustic pressure between the oval window and round window is noted and increased by 5 dB by blocking the aditus. These results suggest that our complete FE model including the mastoid cavity is potentially useful and can provide more information in the study of middle ear biomechanics.